Current perspective of the renewable energy development in Malaysia - Salsabila, Ahmad; Mohd Zainal Abidin, Ab Kadir; Suhaidi, Shafie (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/